POTRET KRITIK SOSIAL DALAM CERPEN "MALAM LAKSMITA"KARYA S PRASETYO UTOMO - dan Elfa Oprasmana, Suhardi (Sasando, 2020)
This research aims to photograph social criticism that is contained in the night story Laksmita Karta S. Prasetyo Utomo. This research is a qualitative-based study. The technique of data collection using document technique, i.e. Laksmita night short story by S Prasetyo Utomo. While the analysis of data using the content analysis technique is to read and understand the contents of the short story and analyze it based on social short story. The results obtained are short stories of "Malam Laksmita" by S. Prasetyo Utomo contain social criticism, in the form of: Criticism (1) religion, especially Islam, (2) culture, (3) economics; and critique (3) environment.